Investigating the Practice of Financial Accounting Standards for Micro, Small and Medium Enterprise (Msmes): Evidence from Central Kalimantan - Hafizi, Muhammad Riza; Akbar, Wahyu; Hakim, Sofyan; Misnaningsih, Lusy Nur (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2023)
This study aims to investigate the application of micro and small business financial reports. The approach taken in this research uses using descriptive qualitative method. Qualitative data through semi-structured interviews were collected from 27 main subjects, namely micro and small businesses. The interview lasted between 45 and 60 minutes, in addition to using observation and documentation techniques to investigate further the role of micro and small business reports as corroborating other forms of evidence. At the same time, the data validation technique uses source triangulation techniques for analysis of data collection, reduction, display and verification. The findings of the results of the investigation of the micro and small business financial reports show that micro and small businesses still need to be more optimal in implementing financial reports following the procedures for Micro, Small and Medium Entity Financial Accounting Standards (SAK EMKM). This is evidenced by 27 micro and small business subjects. Only two small business people were interviewed intensively and implemented the management of recording initial financial reporting activities, namely collecting transaction evidence; 25 other micro and small businesses did not record financial reports. This study contributes to the investigation of the application of micro and small business financial reports in the field by exploring the factors that cause the non-application of financial reports according to the Micro, Small and Medium Entity Financial Accounting Standards (SAK EMKM).